2019
DOI: 10.1016/j.iccn.2019.102754
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of long-distance visitors to intensive care units at a regional major trauma centre in the United Kingdom: A cross-sectional survey

Abstract: for invaluable support and guidance throughout the study. We thank Dr David Kidd for his kind assistance in producing figure 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Colleges [1] Australian and New Zealand Intensive Care Society [9] Canadian Medical Standards [10] World Brain Death Project [11] American Academy of Neurology [12] Number adverse events [15]; high financial costs (equipment and personnel); and challenges for the family and friends of the patient (in terms of visitation access and removal from local support networks) [16].…”
Section: Uk Academy Of Royal Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Colleges [1] Australian and New Zealand Intensive Care Society [9] Canadian Medical Standards [10] World Brain Death Project [11] American Academy of Neurology [12] Number adverse events [15]; high financial costs (equipment and personnel); and challenges for the family and friends of the patient (in terms of visitation access and removal from local support networks) [16].…”
Section: Uk Academy Of Royal Medicalmentioning
confidence: 99%
“…This avoids the need for the transfer of patients receiving mechanical ventilation to specialist centres solely for conduct of ancillary tests. Critical care transfers are associated with adverse events [15]; high financial costs (equipment and personnel); and challenges for the family and friends of the patient (in terms of visitation access and removal from local support networks) [16].…”
Section: Uk Academy Of Royal Medical Colleges [1] Australian and New ...mentioning
confidence: 99%
“…45 Similarly, family members supporting adults after major trauma described additional caring responsibilities, 48 and psychological, physical (exhaustion), and financial impacts. 47 Post-traumatic stress type symptoms were common experiences for patients and family members. 39,41,[45][46][47] One study found that the way patients spoke about their major trauma experience could identify psychological distress cues to aid early detection by clinical staff of mental health needs.…”
Section: Summaries Of Research Evidencementioning
confidence: 99%
“…In some situations of critical illness, specifically in geographically rural areas, the critically ill patient requires advanced care services not available at their local hospital to treat intracranial bleed, spinal cord injury ( Burns, 2021 ; Mackie et al, 2014 ), major trauma, vascular emergencies, or acute myocardial infarction ( Burns, 2021 ), and an interfacility transfer (IFT) to an urban centre occurs ( Blackwell, 2002 ; Johnson, 1999 ). Existing literature indicates that an IFT of a critically ill patient to a distant urban centre adds additional stressors for family members ( Burns et al, 2018 ; Kulnik et al, 2019 ; Mackie et al, 2014 ) with stress and anxiety noted to be central constructs of the experience ( Burns & Petrucka, 2020 ). Critical care nurses are well positioned to support family members during this experience ( Frivold et al, 2015 ; International Family Nurses Association (IFNA), 2015 ; Mackie et al, 2014 ).…”
mentioning
confidence: 99%
“…In addition to this limited understanding, Burns and Petrucka (2020) found that healthcare professionals do not view the experiences of family members from rural areas as unique, thereby potentially neglecting their distinct care needs.Regionalization of health care, where secondary and tertiary services are concentrated in select centers (Kahn et al, 2008), has resulted in the necessity of interfacility transfer (IFT) of critically ill patients from general hospitals to distant, specialized hospitals for advanced critical care services (Blackwell, 2002; Canadian Institute for Health Information [CIHI], 2010[CIHI], , 2016. A critically ill patient's IFT has been recognized as generating additional stress for family members (Burns et al, 2018;Kulnik et al, 2019;Mackie et al, 2014), although contributing factors are less understood. According to Mackie et al (2014), family members from rural areas who experience a critically ill relative's IFT to a distant urban center have needs that are distinct from their counterparts in urban 1124254J FNXXX10.…”
mentioning
confidence: 99%